Penggunaan Garam-Garam Kalium sebagai Agen Pengaktifan Kimia bagi Penyediaan Karbon Teraktif daripada Serepai Batang Kelapa Sawit - Hussien, Mohd Zobir; Zainal, Zulkarnain; Lau, Ai Ai; Badri, M. (Universiti Putra Malaysia Press, 1994)
Activated carbon was prepared from the chips of oil palm trunk by destructive distillation under vacuum, using potassium salts at various concentrations, as the chemical activation agent. The chemical and physical properties of the resulting activated carbon showed that the type and the percentage of potassium salts play an important role which determines the properties of the resulting activated carbon.